COMUNIDANZA II: analysis on the Artistic Practice Between Dance, Communities and Social Action - Monestel Chaves, Verónica (2021)
This paper is part of the systematization process of the Comunidanza II project: analysis on the artistic practice between dance, communities and social action, proposed to the dance company of the Universidad de Costa Rica-Danza Universitaria,  in 2020. It aims at the visibility, analysis and re-conceptualization of social action based on the community artistic practices carried out by the group between 2011-2019. It proposes a playful and creative early listening, focused on action, the construction of new mediation methodologies and inclusive and decentralized community development. The links in community action, the body, the interactive nature of dance and its educational component are identified as foundational axes implicit in its practice. Reflection draws on the field of sociology, community art, philosophical anthropology; as well as psychology and education.